Clinical Presentation and Management Strategies in Intraorbital Foreign Bodies - Samreen Khanam; Ayushi Agarwal; Ruchi Goel; Neha Rathie; Akash Raut; Shweta Raghav; Sumit Kumar; Mohit Chhabra; Sonam Singh; Sushil Kumar (Case Reports in Ophthalmological Medicine)
The authors present a retrospective, observational case study of seven patients, who presented with retained Intra-Orbital Foreign Bodies (IOrbFBs) following penetrating orbital injury at a tertiary eye hospital over a period of one year. Cases were reviewed for epidemiological features, mechanism of injury, nature of foreign body, clinical features, imaging modality, associated complications, management outcomes, and the final prognosis. The mean age of presentation was 27.43 years. Amongst the seven patients, two were children (aged <10 years). The male : female ratio was 4 : 3. Of the seven retained IOrbFBs, two were plastic, two wooden, and three metallic in nature (one gunshot injury, one ball projectile (commonly referred to as BB) injury, and one with knife). Two out of seven had no light perception at presentation. The periocular location of the foreign bodies was inferior in 4 cases and medial in 3 cases. Computed Tomography scan confirmed the diagnosis in five cases and Magnetic Resonance Imaging (MRI) was diagnostic in one. Surgical intervention was done in five cases, and two cases were managed conservatively. The authors conclude that favourable outcome can be achieved even without surgical removal in cases of inert metallic/inorganic IOrbFBs. The properties of plastic FBs can frequently render them invisible on imaging, or they may mimic chronic inflammatory conditions like tuberculosis. Long-standing wooden IOrbFBs evade identification radiologically due to prolonged hydration. The ultimate choice of intervention must be individualised, weighing the risks of retention against the risk of iatrogenic damage.